2022
DOI: 10.1007/s40615-022-01415-2
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Variation in COVID-19 Vaccination Uptake Among Medicare Beneficiaries with Cancer History

Abstract: Background The purpose of this study was to estimate COVID-19 vaccination rate among Medicare beneficiaries with cancer history and determine whether COVID-19 vaccine uptake is higher among non-Hispanic White beneficiaries compared with racially and ethnically minoritized beneficiaries. Methods We used US representative, cross-sectional data from the Medicare Current Beneficiary Survey COVID-19 Winter 2021 Rapid Response Community Supplement Survey. A total of 1,863 res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…In contrast, they had 1787 patients with various cancer types, and only 3% (54) were fully vaccinated. In addition, Poghosyan et al found a higher COVID-19 vaccination rate in non-Hispanic White Medicare beneficiaries with cancer histories compared with that in the Black and Hispanic counterparts, which is consistent with our results [39]. Moreover, the percentage of fully vaccinated (66.7%) people in the US population before May 8, 2022, was much higher than that (21.8%) in the GI cancer patients included in our study [40].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, they had 1787 patients with various cancer types, and only 3% (54) were fully vaccinated. In addition, Poghosyan et al found a higher COVID-19 vaccination rate in non-Hispanic White Medicare beneficiaries with cancer histories compared with that in the Black and Hispanic counterparts, which is consistent with our results [39]. Moreover, the percentage of fully vaccinated (66.7%) people in the US population before May 8, 2022, was much higher than that (21.8%) in the GI cancer patients included in our study [40].…”
Section: Discussionsupporting
confidence: 92%